Dampak Penggunaan Meta Artificial Intelligence Pada WhatsApp Terhadap Cara Berpikir Mahasiswa Saat Diskusi di Kelas - Solehudin, Much; Widya Rahmawati Al-Nur (Jurnal Kependidikan, 2025)
The development of the world of technology is now increasingly unstoppable by humans. Of course it is a matter of caution, one of which is for students to be able to use it wisely. The world of education is currently experiencing significant changes in the teaching and learning process, this has been triggered by the development of artificial intelligence (AI) technology. This research aims to determine the impact of using Meta AI on WhatsApp on the way students think during class discussions. The method used in this research is descriptive qualitative with data collection techniques in two ways, the first, field study by making observations and asking questions via Googleform to students, and the second is library study by studying several references in the form of scientific journals, and using the internet as a source of information search. The results of this research show that the use of Meta AI on students' ability to express opinions during class discussions has a relatively balanced impact between positive and negative. The positive impact of meta-AI for students is that it is able to help students find answers when they get questions from the audience. However, on the other hand, the use of Meta AI can reduce students' critical thinking, because with a limited mindset, meta AI can influence the decisions that students have taken. So discussions without meta AI are still important as a means to hone students' abilities to interact, think critically, and express their ideas without dependence on technology.